Meningkatkan Hasil Belajar Siswa pada Materi PLSU dan PTLSV Menggunakan Alat Peraga Limbah Kayu Jati - La Ome (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2015)
This study was aimed at improving the students’ achievement in PLSV and PtLSV subjects using visual aid (colourful beam and cube models) made from wood. These aids were intended to solve the problems of linear equation and inequation of one varible. This action research was conducted at SMP Negeri 1 Raha academic year 2014/2015 trough Planning, Action, Observation, and Reflection Activities. The result showed that the use of coulourful visual aids can improve the students’ achievement. The improvement was shown by the following scores: 65% at Cycle I and 90.6% at cycle II. The teacher class management was 70% at first cycle and 90% at Second cycle. In addition, the students’ activities were 57.1% and 100% at cycle I and cycle II respectively.